The Effect of Patient Complaints on Physicians in European and Commonwealth Countries with Public Healthcare Systems: A Scoping Review and Ethical Analysis - Monteferrante, Erica; Volesky, Karena; Brisson, Julien; Sigman, Harvey; Laliberté, Maude (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
Bioethicists have long advocated for patients’ rights by deliberating on what physicians should or should not do for the well-being of patients. Part of this advocacy has involved challenging a paternalistic medical model where physicians are seen as authoritative figures above reproach. Through ombudsperson offices, patients can submit complaints that may lead to medical examiners conducting detailed examinations of physicians’ conduct and decision-making. Prior research indicates that complaints can have serious and broad effects on physicians. We conducted a scoping review to explore and evaluate the extent of the quantitative and qualitative literature examining the effects of complaints on physicians in European and Commonwealth countries. We systematically searched electronic databases (CINAHL, MEDLINE and PsycInfo) and grey literature for primary research that collected information directly from physicians on at least one potential effect of formal complaints. After screening the titles/abstracts of 14,913 records and reviewing 137 full-texts, 25 studies were included. The 25 studies reported on several potential effects, including the patient-physician relationship (3 studies), defensive medicine (14 studies), anxiety (8 studies), depression (8 studies), one’s identity as a physician (5 studies), and anger (5 studies). Generally, the effects evaluated in the included studies were negative. Although the existing literature covered a range of possible effects, few studies assessed the same effects via different methods, and in different regions and contexts. The findings of this scoping review suggest that complaints processes can have negative effects on physicians.